Converting oil wells to geothermal resources: Roadmaps and roadblocks for energy transformation. (February 2022) - Nadkarni, Kabir; Lefsrud, Lianne M.; Schiffner, Daniel; Banks, Jonathan
Abstract: Geothermal energy systems can make it possible to source sustainable, zero-carbon heat through geothermal direct use. Jurisdictions with mature oil industries and well characterized reservoirs often have the greatest capacity to transition to geothermal energy, yet the same jurisdictions are also most likely to oppose it. Despite technical capabilities, studies show that public perception and policy can be significant limiting factors in geothermal development. We examine how stakeholders' discourses, networks, and resources interact over time to impact the success or failure of geothermal development within France and Alberta as two oil producing regimes. We found that these three elements of agency (discourse, resources, and networks) converge in France versus diverge in Alberta, and that their convergence is defined by their positive interaction with one another over time. We glean important lessons for policymakers interested in promoting energy transformation based on this analysis of the elements of agency in France and Alberta's geothermal case. The three policy recommendations are: policy for mobilizing third-party resources across the stakeholder network to support innovation; policy for aligning discourse about energy use across networks beyond the energy sector; and policy for enabling discourse about new energy resources that recognizes its distinctiveness from other resources. Highlights: We show how agency develops with evolutionary, relational and durational frameworks. We assess how discourse, networks and resources impact geothermal development at oil wells. We find that three elements of agency converge in France and diverge in Alberta. We identify key policy implications for low temperature geothermal innovation. We highlight Alberta's strengths in oil and gas mission-oriented innovation.